Existence of Positive Solutions for Higher Order Boundary Value Problem on Time Scales (Communications in Mathematical Research, 2021)
In this paper, we investigate the existence of positive solutions of a classhigher order boundary value problems on time scales. The class of boundary valueproblems educes a four-point (or three-point or two-point) boundary value problems,for which some similar results are established. Our approach relies on the Krasnosel'skii fixed point theorem. The result of this paper is new and extends previouslyknown results.
Keywords: higher order boundary value problem; positive solution; semipositone; on time scale; fixed point.